The relationship between fatigue and workplace accidents in the construction sector: A statistical study on contributing factors and risk implications - Azzamullah, Aziz; Izzoelhq, Adam; Supeno, Sandi Rafika Alif; Purwoko, Wahyu Alim; Trisnawaty, Devi (Calamity: A Journal of Disaster Technology and Engineering, 2025)
Background: Occupational accidents remain a persistent issue in the construction sector, often associated with various risk factors including worker fatigue. This study aims to analyze the effect of fatigue on the incidence of work accidents in construction projects. Previous studies have shown that fatigue can impair concentration and reaction time, leading to increased accident risks. Methods: This research employed a quantitative descriptive method with data collected through structured questionnaires from 34 construction workers. The data were analyzed using regression analysis. Additionally, instrument testing included validity tests, reliability tests, and linearity tests to ensure the accuracy and consistency of the data. Findings: The results demonstrated that worker fatigue has a significant effect on the occurrence of work accidents (p < 0.05). Factors such as long working hours, insufficient sleep, and heavy workload contributed to fatigue, which in turn increased accident potential. These results align with existing theoretical frameworks linking physical exhaustion to unsafe behaviors and reduced awareness. Conclusion: Fatigue significantly influences the frequency of workplace accidents in construction environments. Effective management of work schedules and adequate rest is essential to minimize these risks. Novelty/Originality of this article: This study offers a statistically validated perspective on the influence of fatigue on construction-related accidents, supported by rigorous instrument testing to ensure reliability and precision of findings, which contributes new empirical evidence to occupational safety literature.